Diversity and phylogenetic composition of bacterial communities and their association with anthropogenic pollutants in sewage sludge. (January 2020) - Stiborova, Hana; Strejcek, Michal; Musilova, Lucie; Demnerova, Katerina; Uhlik, Ondrej
Abstract: Despite wastewater treatment, sewage sludge is often contaminated with multiple pollutants. Their impact on the phylogenetic composition and diversity of prokaryotic communities in sludge samples remains largely unknown. In this study, we analyzed the phylogenetic structure of bacterial communities and diversity in sludge from six waste water treatment plants (WWTPs) and linked this information with the pollutants identified in these samples: eight potentially toxic metals (PTMs) and four groups of organic pollutants [polychlorinated biphenyls (PCBs), polyromantic hydrocarbons (PAHs), brominated flame retardants (BFRs) and organochlorine pesticides (OCPs)]. Alpha diversity measures and the distribution of dominant phyla varied among the samples, with the community from the thermophilic anaerobic digestion (TAD)-stabilized sample from Prague being the least rich and the least diverse and containing on average 36% of 16S rRNA gene sequence reads of the thermotolerant genus Coprothermobacter of the class Clostridia (phylum Firmicutes). Using weighted UniFrac distance-based redundancy analysis (dbRDA), we found that a collection of 5 PTMs: Cr, Cu, Ni, Pb, Zn, and a pair of BFRs: hexabromocyclododecane (HBCD) and tribromodiphenyl ethers (triBDEs) were significantly associated with the bacterial community structure in mesophilic anaerobic digestion (MAD)-stabilized samples, whereas PCBs were observed to be marginally significant. Altogether, 85% of the variance in bacterial community structure could be ascribed to these pollutants. The data presented here contribute to a greater understanding of the ecological effects of combined pollution on the composition and diversity of bacterial communities, hence have the potential to aid in predicting ecosystem functions and/or disruptions associated with pollution. Highlights: Association of bacterial communities with pollutants in sewage sludge is described. 5 metals were significantly associated with the bacterial community structure. Two brominated flame retardants were associated with the community structure. 85% of the variance in bacterial community structure could be ascribed to these pollutants.